Comparative study of complement protein activity of blood serum against Shigella flexneri in urban and slum population of Bangladesh - Rahman, Sarjana Bilkis (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirement for the degree of B.Sc in Microbiology, 2016.